2014
DOI: 10.5935/0034-7167.20140002
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding difficulties and influence in the early weaning

Abstract: RESUMOO estudo objetivou verifi car o tempo médio do aleitamento materno exclusivo (AME) de crianças nascidas em Hospital Amigo da Criança (IHAC) e correlacioná-lo com as variáveis: estado civil, idade materna, peso do bebê, difi culdades na amamentação e orientações recebidas. Trata-se de estudo de coorte com amostra de 225 mães entrevistadas no puerpério mediato e no 15º, 30º, 60º, 120º e 180º dias após a alta, por telefone. O monitoramento do AME demonstrou mediana de 113 dias e que 34,1% das mães aleitaram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 11 publications
5
11
0
14
Order By: Relevance
“…Corroborating the data found in the study [10] developed in a tertiary public maternity hospital of the Northeast Region of Brazil, which found a mean maternal age of 26±7 years in their results, and the study that found a mean age of 25.7 years [11].…”
Section: Discussionsupporting
confidence: 64%
“…Corroborating the data found in the study [10] developed in a tertiary public maternity hospital of the Northeast Region of Brazil, which found a mean maternal age of 26±7 years in their results, and the study that found a mean age of 25.7 years [11].…”
Section: Discussionsupporting
confidence: 64%
“…The percentage of 79% of children being exclusively breastfed, identified in this study, can be considered adequate, since the WHO attributes this concept when 50% to 89% of children under six months of age are exclusively breastfed. (11) The application of the scale allowed to identify that mothers presented high and moderate efficacy and none of them obtained results consistent with low self-efficacy.…”
Section: Sd -Standard Deviationmentioning
confidence: 99%
“…(11) Rates of exclusive breastfeeding in Brazil are on a rise, but still below what is recommended by the WHO, which is 180 days. The percentage of 79% of children being exclusively breastfed, identified in this study, can be considered adequate, since the WHO attributes this concept when 50% to 89% of children under six months of age are exclusively breastfed.…”
Section: Sd -Standard Deviationmentioning
confidence: 99%
“…A similar result was identified in a hospital with the title of IHAC, in São Paulo, Brazil [11]. Researchers revealed that, regardless of obstetric conditions, one-third of the primiparous and multiparous women with or without experience who sought to breastfeed failed to initiate it, which requires educational efforts directed towards support for both groups [12].…”
Section: Discussionmentioning
confidence: 52%